A Comparative Study on the Effect of Different Methods of Recycling Orthodontic Brackets on Shear Bond Strength. (21st January 2021) - Khanal, Purna Prasad; Shrestha, Basanta Kumar; Yadav, Rajiv; Prasad Gupta, Dr. Sanjay
Abstract : Aim . The aim of this study was to evaluate and compare the effect of different methods of recycling stainless steel orthodontic brackets on shear bond strength. Methods . One hundred twenty human premolars extracted for orthodontic purpose were randomly divided into four groups. Standard MBT (0.022″) brackets were bonded on the buccal surface of all samples with light cured adhesive primers using an LED curing unit for 10 seconds. Group I was assigned as control, and the brackets of Group II, Group III, and Group IV were subjected to recycling by flaming, flaming with sandblasting, and flaming with ultrasonic cleaning, respectively. The recycled brackets were rebonded, and final debonding of all brackets was performed using a universal testing machine at a crosshead speed of 0.5 mm/min and shear bond strength was determined. Data were analyzed with descriptive statistics, ANOVA, and post hoc tests. The adhesive remnant index was evaluated using a stereomicroscope at 10X magnification. Results . The highest shear bond strength was obtained with Group I (10.35 ± 0.46 MPa), followed by Group III (9.36 ± 0.55 MPa) and Group IV (5.97 ± 0.66 MPa), and the least value was obtained with Group II (4.30 ± 0.55 Mpa). Significant differences among the groups were detected by analysis of variance. Tukey's post hoc multiple comparison test showed that the shear bond strength of each group was significantly different from one another (p < 0.001 ). Conclusions . Shear bond strength of new brackets was significantly higher than that of the recycled brackets. Among recycled brackets, flaming with sandblasting provided adequate shear bond strength, flaming with ultrasonic cleaning provided a borderline value for clinical use, and flaming alone led to a significantly lower value.